The marketing in crisis situations on the example of the volleyball club AZS Częstochowa SSA - Kowalski, Sławomir (Quality in Sport, 2018)
The basic objective of the article is to define the main directions of development of sports marketing in crisis situations. The article is also aimed at showing marketing activities and using the method of influencing current and potential fans. The basic research subject is the volleyball men’s club AZS Częstochowa SSA. The article analyzes the effects of marketing activities after the fall from PlusLiga and their analysis in terms of effectiveness based on data from the surveyed Club. The basic results contained in the article are specific corrective actions and their model presentation. In practice, that analyze can be used to build a new identity and marketing policy in crisis situations, such as a degradation to a lower class or a lower level of sport. The presented information and their analysis are an original attempt of a model approach to sports club management and its values in difficult situations from a marketing point of view.